2016
DOI: 10.1016/j.neubiorev.2015.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Neuroimaging markers of glutamatergic and GABAergic systems in drug addiction: Relationships to resting-state functional connectivity

Abstract: Drug addiction is characterized by widespread abnormalities in brain function and neurochemistry, including drug-associated effects on concentrations of the excitatory and inhibitory neurotransmitters glutamate and gamma-aminobutyric acid (GABA), respectively. In healthy individuals, these neurotransmitters drive the resting state, a default condition of brain function also disrupted in addiction. Here, our primary goal was to review in vivo magnetic resonance spectroscopy and positron emission tomography stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 172 publications
(217 reference statements)
1
37
0
Order By: Relevance
“…Particularly germane to the present topic, animal models have led to important findings on neural substrates mediating addiction to multiple substances of abuse (c.f., Bell and Rahman, 2016; De Biasi, 2015; Dwoskin, 2014; Ekhtiari and Paulus, 2016a, 2016b; Frascella et al, 2011; Heidbreder, 2008; Koob et al, 2014a; McArthur and Borsini, 2008c; Nader, 2016; Olmstead, 2011) and ethanol in particular (Bell et al, 2005, 2006b, 2012, 2013, 2014, 2016; Ciccocioppo, 2013; Crabbe et al, 2013; Knapp and Breese, 2012; Maldonado-Devincci et al, 2012; McBride and Li, 1998; McBride et al, 2014b; Ramsden, 2015; Ryabinin, 2012). As indicated above, advanced neuroimaging techniques including resting state functional connectivity are being used to develop endophenotypes for medications development targeting AUDs (e.g., Brown et al, 2015; Cui et al, 2015; Ernst et al, 2015; Fedota and Stein, 2015; Gowin et al, 2015; Gullo et al, 2011; Moeller et al, 2016; Muller-Oehring et al, 2015a, 2015b; Schuckit et al, 2016; Squeglia et al, 2014). In general, an animal model has the advantage of allowing the experimenter to control factors such as the animal's genetic background, environment, and drug exposure.…”
Section: Background From An Animal Model Perspectivementioning
confidence: 99%
“…Particularly germane to the present topic, animal models have led to important findings on neural substrates mediating addiction to multiple substances of abuse (c.f., Bell and Rahman, 2016; De Biasi, 2015; Dwoskin, 2014; Ekhtiari and Paulus, 2016a, 2016b; Frascella et al, 2011; Heidbreder, 2008; Koob et al, 2014a; McArthur and Borsini, 2008c; Nader, 2016; Olmstead, 2011) and ethanol in particular (Bell et al, 2005, 2006b, 2012, 2013, 2014, 2016; Ciccocioppo, 2013; Crabbe et al, 2013; Knapp and Breese, 2012; Maldonado-Devincci et al, 2012; McBride and Li, 1998; McBride et al, 2014b; Ramsden, 2015; Ryabinin, 2012). As indicated above, advanced neuroimaging techniques including resting state functional connectivity are being used to develop endophenotypes for medications development targeting AUDs (e.g., Brown et al, 2015; Cui et al, 2015; Ernst et al, 2015; Fedota and Stein, 2015; Gowin et al, 2015; Gullo et al, 2011; Moeller et al, 2016; Muller-Oehring et al, 2015a, 2015b; Schuckit et al, 2016; Squeglia et al, 2014). In general, an animal model has the advantage of allowing the experimenter to control factors such as the animal's genetic background, environment, and drug exposure.…”
Section: Background From An Animal Model Perspectivementioning
confidence: 99%
“…Studies have shown that addicted individuals tended to show decreases in the glutaminergic system compared with healthy controls. Moreover, select corticolimbic brain regions showing glutamatergic and/or GABAergic abnormalities have been similarly implicated in resting-state functional connectivity deficits in drug addiction (186). There are many studies showing impairments of resting state functional connectivity with alcohol, opiates, cannabis, psychostimulants, nicotine, glucose and even some of the behavioral addictions, further suggesting the need to find compounds that will restore normal resting state functional connectivity (6,(187)(188)(189)(190)(191)(192)(193)(194)(195)(196)(197)(198)(199)(200).…”
Section: Summary and Perspectivesmentioning
confidence: 99%
“…We are in agreement with the concept that resting state functional connectivity may have clinical relevance crucial to the development of and risk for all RDS behaviors. Studies have shown that addicted individuals tended to show decreases in the glutaminergic system compared to healthy controls (262). Moreover, select corticolimbic brain regions showing glutamatergic and/or GABAergic abnormalities have been similarly implicated in restingstate functional connectivity deficits in drug addiction (262).…”
Section: Gentile Pro Dopamine Therapy: With Glutaminergic-dopaminergimentioning
confidence: 99%
“…Studies have shown that addicted individuals tended to show decreases in the glutaminergic system compared to healthy controls (262). Moreover, select corticolimbic brain regions showing glutamatergic and/or GABAergic abnormalities have been similarly implicated in restingstate functional connectivity deficits in drug addiction (262). There are many studies showing impairments of resting state functional connectivity with alcohol, opiates, cannabis, psychostimulants, nicotine, glucose, and even some behavioral addictions, further suggesting the need to find compounds that will restore normal resting state functional connectivity (263)(264)(265)(266)(267)(268)(269)(270)(271)(272)(273)(274)(275)(276)(277).…”
Section: Gentile Pro Dopamine Therapy: With Glutaminergic-dopaminergimentioning
confidence: 99%